THE ROLE OF ULAMA IN CRIMINAL POLICY FORMATION IN INDONESIA - Christine Olidita Indahrami Sanggenafa; Aslan Aslan (INJOSEDU: International Journal of Social and Education, 2025)
The role of ulama in the formation of criminal policy in Indonesia is a form of integration of religious values with the national legal system. As religious authorities, ulama have the responsibility to convey views based on the principles of justice, protection of victims, guidance of criminals, and crime prevention in line with spiritual approaches. Through their input to policymakers, ulama contribute to creating harmony between positive law and religious law. This approach aims to make criminal policy more acceptable to society and effective in combating crime. However, challenges arise in accommodating Indonesia's pluralistic socio-cultural diversity, which requires synergy between ulama, government and legal experts to create policies that are just, inclusive and in line with universal values. This study emphasises the importance of multidisciplinary collaboration for a legal system that is responsive to the aspirations of society.